2017
DOI: 10.1002/hbm.23657
|View full text |Cite
|
Sign up to set email alerts
|

The experience of beauty derived from sorrow

Abstract: We studied the neural mechanisms that are engaged during the experience of beauty derived from sorrow and from joy, two experiences that share a common denominator (beauty) but are linked to opposite emotional valences. Twenty subjects viewed and rerated, in a functional magnetic resonance imaging scanner, 120 images which each had classified into the following four categories: beautiful and sad; beautiful and joyful; neutral; ugly. The medial orbito‐frontal cortex (mOFC) was active during the experience of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…A recent functional magnetic resonance imaging study by Ishizu and Zeki (2017), researching brain networks during enjoyment of emotionally negatively and positively valenced artistic photographs, supports the above argument. Both positive and negative photographs that were experienced as aesthetically preferable coincided with higher activation in brain reward areas.…”
Section: Boris Egloffmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent functional magnetic resonance imaging study by Ishizu and Zeki (2017), researching brain networks during enjoyment of emotionally negatively and positively valenced artistic photographs, supports the above argument. Both positive and negative photographs that were experienced as aesthetically preferable coincided with higher activation in brain reward areas.…”
Section: Boris Egloffmentioning
confidence: 75%
“…Second, our model proposes a new, integrative perspective on existing theorizing and available empirical data, but it does not provide any new data. To our knowledge, neuroscientific research on coactivations of negative emotions and feelings of reward is only beginning, and several pertinent studies (Brattico et al 2016;Ishizu & Zeki 2017;Wassiliwizky et al 2017b; see also the commentary by Brattico & Vuust) were only published after the acceptance of our article. As a result, we cannot but agree with the comment by Nadal, Vartanian, & Skov (Nadal et al) that our model does not provide a "neurobiological basis" for the topic under consideration.…”
Section: R1 Introductionmentioning
confidence: 99%
“…Again, the precuneus has been found to be involved in art appreciation and the expectation of reward (Doñamayor, Schoenfeld, & Münte, ; Mizokami et al, ). The mOFC has been strongly implicated in rewarding emotional experience of visual and musical stimuli (Ishizu & Zeki, , , ; O'Doherty et al, ; Zeki, Romaya, Benincasa, & Atiyah, ). Given the strong associations between these two brain regions and rewarding emotional experience, our results suggested that perceiving landscape gardens is rewarding.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, therefore, a much more useful approach to the definition of beauty would be one that has its source in the results of neurobiological studies of the experience of beauty derived from different sources; these include sensory (Izhizu & Zeki, 2011), moral and highly cognitive (Zeki, Romaya, Benincasa & Atiyah, 2014) ones, as well as sensory experiences that have harmonious relationships (in colour) (Ikeda et al, 2015) and opposite emotional valences (such as joy and sorrow) (Ishizu & Zeki, 2017). The experience of beauty, and even a memory of it , derived from all these sources correlates with activity in a given, specific, part of the emotional brain, namely, field A1 of the medial orbitofrontal cortex (A1mOFC) (Figure 1).…”
Section: A Neurobiological Definition Of Beautymentioning
confidence: 99%